English Learning Difficulties for Multilingual Student: A Case Study of an Indonesian Student in Learning English - Girindra Putri Ardana Reswari (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
The purpose of this research is to help the learner as a multilingual student in improving her English by understanding a particular learner’s strength and weaknesses in speaking and writing. Single case study is used as a method. Steps in conducting this research are initial interview, analysis of spoken data, and also analysis of written data. The results of the interview, spoken and written data being discussed in detail using previous research and theories as literature research. Results of the research showed that some mistakes in her writing and speaking are influenced by her L1 or in this case Bahasa Indonesia.Keywords: single case study; speaking; writing; multilingual